If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9w+18=6(w+5)
We move all terms to the left:
9w+18-(6(w+5))=0
We calculate terms in parentheses: -(6(w+5)), so:We get rid of parentheses
6(w+5)
We multiply parentheses
6w+30
Back to the equation:
-(6w+30)
9w-6w-30+18=0
We add all the numbers together, and all the variables
3w-12=0
We move all terms containing w to the left, all other terms to the right
3w=12
w=12/3
w=4
| 105=x+113 | | t/7–47=-40 | | 5+4x+3x=-65 | | 3x-6+7x=-2+10x+5 | | -4=8(w-6)+3w | | 4.9g+9=2.9g+19 | | 6(2x-5)=-(x=4) | | x(x-10)=144 | | 3t2-12t-15=0 | | c/3+-24=-27 | | 6=-3y+6(y+3) | | 3t2-12t-5=0 | | X=2y=4 | | -25a-35=-5(4a+13) | | 7(v-8)+2v=34 | | s/5+-63=-70 | | 10x-40=7x | | 80=3^n-1 | | 1/4x-10=15 | | 2x-3+7x=3x+27 | | 3x*2+8x-2=0 | | 4(2x+1)=32 | | 6x^2-59x+45=0 | | -3=q-5 | | 4.7=g3.2 | | 8a-7=4a=9 | | 6(x+1)+4=2x+4(2+x) | | 3x+(x+5)=5x-(3+2x) | | x+(x-8)=44 | | x+.05x=21.85 | | -8/x+2-7/x=-5/x+2 | | 12-7/x=-12 |